1996
DOI: 10.1177/00220345960750111001
|View full text |Cite
|
Sign up to set email alerts
|

Taste Preference for Sweetness in Urban and Rural Populations in Iraq

Abstract: The consumption of sweetened foods is influenced by a variety of biological, psychological, sociological, and environmental factors. On an individual level, taste preference for sweetness has been shown to have an influence on food consumption, although this may be affected by social and environmental factors. The aim of this study was to assess the taste preference for sweetness in urban and rural populations in Iraq. The hypothesis was that sweet preference and the consumption of sugar increase with urbaniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
0
31
1
4
Order By: Relevance
“…In this study, the solution with the highest concentration of sugar (E) was the one preferred by the majority of the volunteers, irrespective of gender, a result differing from the findings of Honkala et al 17 and Nilsson & Holm 18 . The taste pattern of preference for sweeter solutions, and consequently, higher sugar consumption has been related in the literature to higher levels of caries 10,19 . However, in this study, this association could not be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the solution with the highest concentration of sugar (E) was the one preferred by the majority of the volunteers, irrespective of gender, a result differing from the findings of Honkala et al 17 and Nilsson & Holm 18 . The taste pattern of preference for sweeter solutions, and consequently, higher sugar consumption has been related in the literature to higher levels of caries 10,19 . However, in this study, this association could not be observed.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of sweetened foods is influenced by a variety of biological, psychological, social and environmental factors. It has been suggested that there is a preference for sweets in populations with worse socioeconomic conditions 10 . Knowing the cariogenic power of fermentable carbohydrates, especially sugar, it makes it necessary to know the dietary habits of the population, in order to develop public policies, adopt efficient preventive methods, in addition to encouraging changes towards developing healthier habits 11 .…”
Section: Conclusãomentioning
confidence: 99%
“…Merece destaque a afirmação de Jamel et al 46 sobre o fato de a preferência pelo açúcar ser altamente influenciada pela maior exposição e disponibilidade desse produto associada à urbanização. Além disso, hábitos adquiridos na infância influenciam fortemente o padrão alimentar durante os anos subseqüentes, podendo tornar-se permanentes 47,48 .…”
Section: Discussionunclassified
“…Um padrão gustativo de preferência para soluções mais adoçadas e conseqüente maior consumo de açú-car tem sido relacionado a níveis mais altos de cárie 6 . Porém, a associação entre a ausência de cárie e a preferência por açúcar não foi observada no presente estudo (Tabela 6).…”
Section: Discussionunclassified
“…Pelo contrário, a preferência por açú-car é altamente influenciada pela exposição aumentada e maior disponibilidade de açúcar associada à urbanização 6 . Isto tem importantes implicações para o desenvolvimento de políticas públicas com o objetivo de promover uma alimentação mais saudável…”
Section: Discussionunclassified